PERANCANGAN BRANDING KABUPATEN LAMONGAN SEBAGAI STRATEGI PROMOSI UNTUK KHALAYAK UMUM - Costa Rica El Chidtian, Aileena Solicitor; Saputro, Karnedy; Nabilah, Bagassani Eka; Sakti, Falah Raka; Bukamo, Mahrawi; Muhammad, Septa Estaffa (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
Lamongan Regency is a regency in East Java province that has promising potential in tourism and agriculture. The more dominant potential in Lamongan Regency is from pond farming, but in Lamongan Regency does not yet have a brand identity for this potential. One way to introduce the potential in Lamongan Regency is by doing city branding. In designing this research using quantitative and qualitative research methods, the researcher obtained data using a questionnaire for the audience and conducted a documentation study and direct observation in the field. The purpose of this design is to improve and introduce a new image of Lamongan Regency so that the community can understand the potential that exists in Lamongan Regency.Key Words: Branding, Tourism, Lamongan Bahari, Identity